1123. EDP-235, A Potent and Once-daily Oral Antiviral, Demonstrates Excellent Penetration into Macrophages and Monocytes, with the Potential for Mitigation of Cytokine Storm in High-Risk COVID-19 Patients. (15th December 2022) - Li, Yang; Zang, Tianzhu Indy; Xu, Lisha; Leonard, Daniel; Hoang, Khanh; Greizer, Tim; Zhang, Shucha; Foster, Caroline; Huang, Meng; Kibel, Jonathan; Klaene, Joshua; Or, Yat Sun; et al.
Abstract: Background: Macrophages, including lung alveolar macrophages (AM), and monocytes are the first lines of defense against SARS-CoV-2. Several reports have suggested that SARS-CoV-2 can hijack AM and monocytes for replication and viral spread, which may, in turn, drive the cytokine storm associated with severe COVID-19. Herein, we describe one of many advantageous features that EDP-235, a novel and potent SARS-CoV-2 3C-like protease (3CLpro) inhibitor under development as a once-daily oral antiviral therapy for COVID-19, displays - excellent penetration into macrophages and monocytes. Methods: Intracellular uptake of EDP-235 was tested side-by-side with nirmatrelvir in rat lung AM, human monocytes and human macrophages. To determine the in vivo drug distribution into lung AM, rats were dosed orally with 25 mg/kg of EDP-235 or nirmatrelvir and plasma and AM drug levels were analyzed by LC/MS/MS. Results: The ratios of intracellular to extracellular concentrations of EDP-235 in rat lung AM, human monocytes and human macrophages were 22.8, 22.7 and 30.5, respectively. In contrast, nirmatrelvir had ratios of 1.2 to 1.5 in these cells. Consistent with the in vitro observations, EDP-235 showed favorable rat AM penetration with an AUC0-24 ratio of 28.4 (AM over plasma), and nirmatrelvir had much less rat AM penetration with an AUC0-24 ratio of 0.5 (AM over plasma). EDP-235 had respective AUC0-24 values of 9.6 and 271.9 h·μg/mL in rat plasma and AM, while the AUC0-24 values of nirmatrelvir in rat plasma and AM were 2.7 and 1.2 h·μg/mL, respectively. Conclusion: EDP-235, a novel and potent SARS-CoV-2 3CL protease inhibitor, demonstrated excellent penetration into monocytes and macrophages, including lung AM. EDP-235 has the potential to eliminate the viral replication of SARS-CoV-2 in these critical immune cells, thus mitigating macrophage-mediated cytokine storm in high-risk COVID-19 patients. Clinical trials with EDP-235 for COVID-19 treatment and prevention are ongoing. Disclosures: All Authors : No reported disclosures.